2022
DOI: 10.3390/cells11233939
|View full text |Cite
|
Sign up to set email alerts
|

Phytocannabinoids Stimulate Rejuvenation and Prevent Cellular Senescence in Human Dermal Fibroblasts

Abstract: In light of the increased popularity of phytocannabinoids (pCBs) and their appearance in beauty products without rigorous research on their rejuvenation efficacy, we decided to investigate the potential role of pCBs in skin rejuvenation. Utilizing healthy and stress-induced premature senescent (SIPS) CCD-1064Sk skin fibroblasts, the effects of pCBs on cellular viability, functional activity, metabolic function, and nuclear architecture were tested. Both delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 63 publications
2
14
0
2
Order By: Relevance
“…We found that the incorporation of the CBD/HP-β-CD complex into the fibroin film markedly enhanced the proliferation of the cells. These findings align with a previous study indicating CBD’s dose-dependent promotion of human dermal fibroblast growth [ 28 ] and prove our hypothesis on the synergistic interplay between fibroin and CBD. Regarding cell proliferation in relation to the cell cycle, these results are in concordance with our previous study in which fibroin exerted potential effects on cell division or G2/M phase [ 8 ], and they also align with the proliferation results obtained in this current study.…”
Section: Discussionsupporting
confidence: 93%
“…We found that the incorporation of the CBD/HP-β-CD complex into the fibroin film markedly enhanced the proliferation of the cells. These findings align with a previous study indicating CBD’s dose-dependent promotion of human dermal fibroblast growth [ 28 ] and prove our hypothesis on the synergistic interplay between fibroin and CBD. Regarding cell proliferation in relation to the cell cycle, these results are in concordance with our previous study in which fibroin exerted potential effects on cell division or G2/M phase [ 8 ], and they also align with the proliferation results obtained in this current study.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we demonstrated that DMSO-induced oxidative stress is accompanied by the inhibition of SIRT3 and SOD2 and that LnHS prevented the downregulation of both enzymes induced by DMSO. Previously, a modulation of SIRT proteins had been highlighted but only by phytocannabinoids and never by the lignamide fraction ( Gerasymchuck et al, 2022 ; Wang et al, 2022 ). Similarly, the effects of hemp extracts on the modulation of IL-8 have been found for phytocannabinoids but not considering different extracts and cellular models such as lung epithelial cells, macrophages, and human keratinocytes ( Anil et al, 2021 ; Suryavanshi et al, 2022 ; Tortolani et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Topical cannabinoid preparations have therapeutic interest due to their anti-inflammatory, antioxidative, antiacne, anti-UVA/UVB damage, and antimicrobial properties in multiple studies. 110,111 When applied topically, cannabis preparations exert their effects by targeting the components of the ECS in the skin, including epidermal keratinocytes, cutaneous nerve fibers, dermal cells, melanocytes, eccrine sweat glands, and hair follicles. 112 By interacting with numerous receptors, including CB1, CB2, peroxisome proliferatoractivated nuclear receptors, and TRP channels, cannabinoids modulate vital processes to support the skin barrier, including anti-inflammatory, analgesic, and neuroprotective cellular effects.…”
Section: Topical and Transdermalmentioning
confidence: 99%
“…Topical cannabinoid preparations have therapeutic interest due to their anti‐inflammatory, antioxidative, antiacne, anti‐UVA/UVB damage, and antimicrobial properties in multiple studies 110,111 . When applied topically, cannabis preparations exert their effects by targeting the components of the ECS in the skin, including epidermal keratinocytes, cutaneous nerve fibers, dermal cells, melanocytes, eccrine sweat glands, and hair follicles 112 .…”
Section: Modes Of Administration and Pharmacokinetic Considerationsmentioning
confidence: 99%